The Child Opportunity Index and Disparities in Pediatric Asthma Hospitalizations Across One Ohio Metropolitan Area, 2011-2013 - Beck, Andrew F.; Huang, Bin; Wheeler, Kathryn; Lawson, Nikki R.; Kahn, Robert S.; Riley, Carley L. (The Journal of pediatrics, 2017)
To determine whether the Child Opportunity Index (COI), a nationally available measure of relative educational, health/environmental, and social/economic opportunity across census tracts within metropolitan areas, is associated with population- and patient-level asthma morbidity. This population-based retrospective cohort study was conducted between 2011 and 2013 in a southwest Ohio county. Participants included all children aged 1-16 years with hospitalizations or emergency department visits for asthma or wheezing at a major pediatric hospital. Patients were identified using discharge diagnosis codes and geocoded to their home census tract. The primary population-level outcome was census tract asthma hospitalization rate. The primary patient-level outcome was rehospitalization within 12 months of the index hospitalization. Census tract opportunity was characterized using the COI and its educational, health/environmental, and social/economic domains. Across 222 in-county census tracts, there were 2539 geocoded hospitalizations. The median asthma-related hospitalization rate was 5.0 per 1000 children per year (IQR, 1.9-8.9). Median hospitalization rates in very low, low, moderate, high, and very high opportunity tracts were 9.1, 7.6, 4.6, 2.1, and 1.8 per 1000, respectively (P < .0001). The social/economic domain had the most variables significantly associated with the outcome at the population level. The adjusted patient-level analyses showed that the COI was not significantly associated with a patient's risk of rehospitalization within 12 months. The COI was associated with population-level asthma morbidity. The details provided by the COI may inform interventions aimed at increasing opportunity and reducing morbidity across regions.